Analisis Pengaruh Keselamatan Kerja Dan Pelatihan Terhadap Kinerja Karyawan - M. Deny Irawan; M. Arif Wicaksono; Ayu Lucy Larassaty (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This article examines research on how employee performance is affected by safety and workplace training. Occupational safety (X1) Employee performance (Y) Training (X2) Employee performance (Y) are findings from literature research. The purpose of this research is to identify and evaluate the relationship between work safety and employee performance. The prerequisite for increasing employee work productivity that is directly related to output production is performance safety. The study's qualitative methodology produces data that includes an examination of employee performance and work safety. In short, if there is protection from guaranteed work safety, then work safety is the main factor to avoid accidents involving the environment, materials, equipment, as well as labor and employee performance.